PERBANDINGAN KEEFISIENAN METODE NEWTON-RAPHSON, METODE SECANT, DAN METODE BISECTION DALAM MENGESTIMASI IMPLIED VOLATILITIES SAHAM - RAHAYUNI, IDA AYU EGA; DHARMAWAN, KOMANG; IDA HARINI, LUH PUTU (E-Jurnal Matematika, 2016)
Black-Scholes model suggests that volatility is constant or fixed during the life time of the option certainly known. However, this does not fit with what happen in the real market. Therefore, the volatility has to be estimated. Implied Volatility is the etimated volatility from a market mechanism that is considered as a reasonable way to assess the volatility's value. This study was aimed to compare the Newton-Raphson, Secant, and Bisection method, in estimating the stock volatility value of PT Telkom Indonesia Tbk (TLK). It found that the three methods have the same Implied Volatilities, where Newton-Raphson method gained roots more rapidly than the two others, and it has the smallest relative error greater than Secant and Bisection methods.
Keywords: Black-Scholes; Implied Volatility; Newton-Raphson Method; Secant Method; Bisection Method